Livestock feed resources used as alternatives during feed shortages and their impact on the environment and ruminant performance in West Africa: a systematic review - Alimi, Nouroudine; Assani, Alassan S.; Sanni Worogo, Hilaire; Baco, Nasser Mohamed; Traoré, Ibrahim Alkoiret (Frontiers in Veterinary Science, 2024)
Ruminant feed is a major problem for the livestock sector in West African developing countries causing animal nutritional diseases, reducing ruminant production, and creating a massive ecological crisis through greenhouse gas emissions. Alternative feeds, which include agro-industrial by-products, fodder trees, crop residues, insects, fodder legumes, algae, and pulses, constitute enormous feed resources for livestock in Africa. This study was conducted in accordance with the methodological recommendations of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). We conducted a literature search using Google Scholar, Web of Science, and Scopus to identify documents related to alternative ruminant feeds using the following keywords: alternative feeds, ruminant products, environmental impacts, and West Africa. Those that met the inclusion criteria were included, resulting in 44 articles published between 2013 and 2023. These studies included 45 alternative feeds divided into six groups, including agro-industrial by-products (48.89%), followed by fodder trees (17.78%), crop residues (13.33%), insects (8.89%), fodder legumes (6.67%) and seaweeds (4.44%). Our results revealed that alternative feed resources and their effects on ruminant’s performances and environment are poorly known in West Africa, which limits their inclusion in rations and sometimes leads to their misuse. Future research should focus on these aspects in order to make efficient use of these resources to improve ruminant milk and meat production.